Site of Action of Lipid A on Mitochondria - Kato, Masahiko (1972)
Lipopolysaccharide (LPS) of a number of gram-negative bacteria affected mitochondrial respiration and phosphorylation when it was preincubated with the mitochondrial suspension. The structural part responsible for this activity of LPS is the lipid moiety (lipid A), because the lipid A prepared from either the LPS of Escherichia coli or the endotoxic glycolipid of a heptose-less mutant (R595) of Salmonella minnesota affected mitochondrial oxidative phosphorylation as did LPS, whereas the polysaccharide moiety was inactive. Preincubation of the mitochondrial suspension with lipid A resulted in (i) inhibition of respiration and accompanying phosphorylation in the presence of either succinate or a number of reduced nicotinamide adenine dinucleotide-linked substrates, (ii) decrease of respiratory control, (iii) inhibition of the transfer of electrons at coupling site II without decrease of efficiency of phosphorylation, and the uncoupling at coupling site III, and (iv) stimulation of adenosine triphosphatase and the inhibition of 2,4-dinitrophenol-induced adenosine triphosphatase.